One more for Christmas - Morgan, Sarah, 1948- (HQN, 2020)
A brush with mortality compels a tough-love businesswoman to gather her estranged family for a Christmas reunion in Scotland, where she teams up with her adorable granddaughter to help her daughters reconcile.